2014
DOI: 10.1002/ppap.201400015
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Description of the Chemistry of Thiol Supporting Plasma Polymer Films

Abstract: In this work, the plasma polymerization of propanethiol is investigated with the aim to control the thiol density [SH] in the coatings. The results reveal a nearly constant evolution of [SH] regarding the mean power dissipated in the discharge. This peculiar behavior is explained considering (i) mass spectrometry data revealing a similar relative concentration of condensable SH-bearing species in the plasma and (ii) similar energetic conditions at the growing film/plasma interface. Finally, it is observed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
(168 reference statements)
0
27
0
Order By: Relevance
“…It was proposed that the high production of H 2 S in the discharge and its incorporation into the growing films could account for the variation of the sulfur concentration as a function of the discharge characteristics. 6,7 Among others, it has been shown that the substrate temperature could influence the chemical composition of the coatings. 8 Although poorly studied, the substrate temperature is an important parameter reflecting the energy flux (ionic bombardment, UV photon irradiation, and exothermic surfaces reactions) at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…It was proposed that the high production of H 2 S in the discharge and its incorporation into the growing films could account for the variation of the sulfur concentration as a function of the discharge characteristics. 6,7 Among others, it has been shown that the substrate temperature could influence the chemical composition of the coatings. 8 Although poorly studied, the substrate temperature is an important parameter reflecting the energy flux (ionic bombardment, UV photon irradiation, and exothermic surfaces reactions) at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the comparison between plasma and film chemistries enables to improve the mechanistic understanding of the plasma polymer formation. On this basis, mass spectrometry measurements, in situ FTIR spectroscopy, and in a lesser extent emission spectroscopy have been employed for identifying the species formed through dissociations/rearrangements reactions in the discharge. Although these studies allowed gaining thorough understanding regarding the evolution of the functionality of the coating with respect to the process parameters, some aspects remain unclear, especially concerning the surface reactions.…”
Section: Introductionmentioning
confidence: 99%
“…To explain this behavior, let us first mention that the residence time of the particles in the chamber is much higher than the longest pulse period considered here (i.e., 18 ms for the residence time vs. 2.1 ms for the longest pulse period). Therefore, when increasing t off and hence the pulse period, the molecules are exposed to lower number of plasma “on” time ( t on ) during their residence in the reactor resulting in a less pronounced fragmentation …”
Section: Resultsmentioning
confidence: 99%
“…Today, despite the highly complex growth mechanism of plasma polymer film (PPF) including a multitude of gas phase and surface reactions, it is possible to finely control the chemistry of the PPF using suitable experimental conditions (i.e., low energetic conditions, use of pulsed mode, …) . On the other hand, tailoring the morphology of the PPF at the nanoscale is much more challenging.…”
Section: Introductionmentioning
confidence: 99%